(untitled) (Palimpsesto, 2025)
This article critically analyzes the judicial and institutional practices experienced by parents with intellectual disabilities in Chile, within the framework of legal proceedings related to child custody. Using a qualitative single-case study approach, 171 judicial and intervention program documents were examined, along with six interviews conducted with key stakeholders. The analysis revealed a systematic absence of reasonable accommodations, assessments based on normative models lacking a rights-based perspective, and measures reinforcing discrimination through a punitive approach toward disability. The article concludes that institutional practices reproduce structural exclusions and recommends a shift towards an inclusive paradigm, emphasizing personalized support and intersectoral strategies to ensure the right to family life in conditions of equality and dignity.